2014
DOI: 10.1093/mnras/stu2337
|View full text |Cite
|
Sign up to set email alerts
|

New insights on Ba overabundance in open clusters.★ Evidence for the intermediate neutron-capture process at play?

Abstract: Recently an increasing number of studies were devoted to measure the abundances of neutron-capture elements heavier than iron in stars belonging to Galactic Open Clusters (OCs). OCs span a sizeable range in metallicity (-0.6 ≤ [Fe/H] ≤ +0.4), and they show abundances of light elements similar to disk stars of the same age. A different pattern is observed for heavy elements. A large scatter is observed for Ba, with most OCs showing [Ba/Fe] and [Ba/La] overabundant with respect to the Sun. The origin of this ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
111
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 79 publications
(179 reference statements)
17
111
3
Order By: Relevance
“…On the other hand, in the case of the i process, there is an increase of around a factor of 3 between the production of Sr and that of Zr; and a factor of 10 decrease between Ba and La and/or Ce. In fact, the overproduction of Ba with respect to La resulting from the i process has been pointed out as the possible source of the Ba excess observed in open clusters (Mishenina et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the case of the i process, there is an increase of around a factor of 3 between the production of Sr and that of Zr; and a factor of 10 decrease between Ba and La and/or Ce. In fact, the overproduction of Ba with respect to La resulting from the i process has been pointed out as the possible source of the Ba excess observed in open clusters (Mishenina et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for i-process nucleosynthesis has also been reported in the anomalous Ba enrichment in some open clusters (Mishenina et al 2015), while Dardelet et al (2014) showed that nucleosynthesis in i-process conditions provided a remarkable match to the abundances in several CEMP-r/s (carbon enhanced metal poor with simultaneous presence of s elements and Eu) stars. Possible sites for the i process include the He-core flash (e.g.…”
Section: Introductionmentioning
confidence: 81%
“…Since stars in this mass range are common, this would have important implications for the stellar yields that drive the chemical evolution of stellar clusters and galaxies. For example, these long-lived lowmass stars may be the i-process source required to match observations of [Ba/Fe] and [Ba/La] overabundances in open clusters (Mishenina et al 2015). If the i-process is confirmed to be responsible for the abundances observed in CEMP-s/r and post-AGB stars, similarities and differences in the neutron-capture pattern of the two groups, which sample different metallicity ranges, will provide fundamental constraints to determine its metallicity dependence and its effect on the chemical evolution of stellar systems.…”
Section: Discussionmentioning
confidence: 99%